Potential Impact of Changes in the Schedule for Primary Diphtheria-Tetanus Toxoids-Pertussis Immunization as Control Strategy for Pertussis - Bergero, Paula Elena (2018)
Background: Pertussis is a vaccine-preventable respiratory disease that may cause death mainly in infants. The schedules for primary pertussis vaccination are set in each country by the local health authorities. Several different schedules meet World Health Organization recommendations, 2–4–6 months, 6–10–14 weeks, 2–3–4 months and 3–4–5 months being the most commonly used worldwide. In this work, we analyze the benefits of changing the vaccination schedule to control the disease. Methods: We used an age-structured deterministic mathematical model for pertussis transmission to compute the incidences for the 4 above-mentioned schedules. Different vaccination coverages and vaccine effectiveness levels were considered. Immunization data from Argentina and Belgium were used. Results: The highest reduction in incidence was obtained by adopting the 6–10–14 weeks schedule, reaching about a 36% reduction of 0–1-year incidence with respect to the 2–4–6 months schedule. We show the dependence of this reduction on both vaccine effectiveness and coverage. The severe pertussis incidence decreased significantly when the first dose of the 2–4–6 months schedule was accelerated to 6 weeks. Finally, we estimated that the communication campaign adopted in Flanders (Belgium) to improve compliance with the vaccine schedule could lead to a reduction of 16% in severe pertussis incidence and about 7% in total incidence in infants. Conclusions: Our work highlights the use of mathematical modeling to quantify the benefits of the existing vaccination schedules and the strategies that could be implemented to improve their compliance. Our results indicated that the 6–10–14 weeks is the best schedule option and that the Belgium vaccination campaign significantly reduced the incidence of severe cases.